Unveiling the Potency of Gardenia Extract Against H. pylori: Insights from In Vitro and In Vivo Studies - Pornpen Werawatganone; Duangporn Werawatganon; Nattida Noonak; Maneerat Chayanupatkul; Tanittha Chatsuwan; Naruemon Klaikeaw; Walaisiri Muangsiri; Prasong Siriviriyakul (Biomedicines)
Background and aim: Gardenia jasminoides (G. jasminoides) could treat various inflammatory diseases. This study aimed to investigate the effects of G. jasminoides fruit extract on gastric inflammation and protective mechanisms in Helicobacter pylori (H. pylori)-induced gastritis. Experimental procedure: G. jasminoides fruit extract was prepared and analyzed for geniposide content. The inhibitory effect of the extract on H. pylori growth was investigated using the disk diffusion method. The in vitro anti-inflammatory property of the extract was evaluated using the erythrocyte membrane stabilization method. Thirty-five male Sprague–Dawley rats were inoculated with H. pylori (108–1010 colony-forming unit/mL) and divided into five groups. Each group was treated with various doses of the extract (98–395 mg/kg). The serum and stomach tissue of the rats were evaluated using enzyme-linked immunosorbent assay, histopathology, and immunohistochemistry. Results and conclusions: The geniposide content in the dried extract was 8.12% ± 0.79% by dry weight. The inhibition zone was observed at the extract ≥ 1.97 mg/disk, and the extract presented anti-inflammatory potential. The H. pylori-inoculated rats had a significant increase in serum interleukin (IL)-17, IL-33, and gastric epidermal growth factor (EGF) levels and a significant decrease in serum prostaglandin E2 level (p < 0.05) in conjunction with the development of gastric inflammation on histopathology. The treatment of the extract could significantly decrease the serum IL-17, IL-33, and gastric EGF levels, significantly increase the serum PGE2 level (p < 0.05), and improve gastric histopathology. Thus, G. jasminoides fruit extract attenuated H. pylori-induced gastritis by inhibiting bacterial growth, reducing inflammation, and enhancing protective mechanisms.